Analisis Rencana Anggaran Biaya Pada Proyek Peningkatan Jalan Aur Duri – Rantau Unji (A.Hotmix) Tahap III Sepanjang 3,2 Km Kota Pagar Alam - Sahiman Sahiman; Fameira Dhiniati (JURNAL ILMIAH BERING'S, 2016)
Planning a building must be in accordance with the form and can be useful in its use, and the amount of costs in accordance with the initial calculation. The Budget Plan is planning a building in the form and benefit of its use, along with the necessary costs and implementation arrangements in the field of administration and work implementation in the technical field. The steps taken to calculate the building cost budget plan are identify each existing work item in the project being calculated. In this research the researcher calculates the estimate cost plan with the Bina Marga method, making Work Plan and Terms and time schedule. The research problem formulation is How to calculate the existing budget plan and make a time schedule. The research objective is to calculate the existing estimate cost plan, make a Time Schedule (S Curve) and Work Plan and Terms. The budget plan for the improvement project of Aur Duri - Rantau Unji (a.hotmix) phase III of 2014 is 3.2 km in Pagar Alam City for the general division of Rp. 31,160,000.00, and the total work price of Rp. 1,988,684,545 54, - rounded the amount of Rp. 1,988,684,000.00, -